2000
DOI: 10.3177/jnsv.46.280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graded Levels of Dietary Casein and Corn Oil on Total Cholesterol and Triacylglycerol in Plasma and Liver of Rats.

Abstract: SummaryWith the intention of examining the effects of dietary protein and oil levels on total cholesterol (T-CHOL) and triacylglycerol (TG) concentrations in the plasma and liver, male Wistar rats, weighing about 170g, were fed diets containing graded levels of casein and corn oil for 2 wk. At the 5, 20, and 30% levels of dietary corn oil, plasma T-CHOL con centrations were generally enhanced in proportion to the rise of dietary casein level, but plasma TG contents were scarcely influenced by the level. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Furthermore, LDL‐C values showed an increase in both short‐term (15%) and long‐term (77%) studies (Table 1). In agreement with our findings, Takenchi et al . (2000) have shown that 2‐week feeding of rats on a diet incorporated with 5–30% corn oil had no effect on plasma TAG levels despite an increase on serum TC levels.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Furthermore, LDL‐C values showed an increase in both short‐term (15%) and long‐term (77%) studies (Table 1). In agreement with our findings, Takenchi et al . (2000) have shown that 2‐week feeding of rats on a diet incorporated with 5–30% corn oil had no effect on plasma TAG levels despite an increase on serum TC levels.…”
Section: Discussionsupporting
confidence: 94%
“…2003). For example, Takenchi et al . (2000) reported lipoprotein disorders as a result of feeding rats with corn oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bohm et al (2013) postulated in 2013 that food derived peroxidized fatty acids such as linoleic acid included in WD with corn oil increases hepatic lipid peroxidation and influences immune cells and other pro-inflammatory stimuli that trigger hepatic damage. These findings were corroborated by Takeuchi et al (2000) and Slim et al (1996); finding that corn oil supplementation increased hepatic cholesterol and TG levels and activated the oxidative stress response. On the contrary Si et al (2014) showed 1 year later that a high corn oil diet improved health and longevity in mice by lowering serum lipid levels and decreasing the expression of pro-inflammatory cytokines such as IL-6, IL-1β or MCP-1.…”
Section: Discussionmentioning
confidence: 58%